Pengaruh Pemberian Pestisida Nabati Tanaman Tembakau dan Brotowali terhadap Tingkat Kerusakan Hama Kutu Hijau pada Tanaman Kopi Varietas Robusta di Desa Dompyong, Kecamatan Bendungan Kabupaten Trenggalek - Erlyana Desy Rahmawati; Noni Rahmadhini; Yenny Wuryandari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Green fleas or Coccus viridis (HomopterÐ°: Coccidae) is one of the pests of coffee plants. Pest control efforts can be carred out by using environmentally friendly botanical pesticides. Vegetable pesticides are pesticides whose main ingredients come from plants. The purpose of this study was to determine the effect of giving pesticides from tobacco plants, brotowali plants, and a mixture of the two, with different concentrations on the level of damage to green tick pests on Robusta coffee plants in Dompyong Village, Bendungan District, Trenggalek Regency. This research was carried out in vivo and in vitro. In vivo testing using the RAK method or Factorial Randomized Block Design and then for in vitro testing using the non-factorial RAL method. For in vivo testing there are 6 levels of treatment, each treatment has 4 replications. In vitro testing was carried out in the laboratory with 5 levels of treatment and there were 4 replications. The application of botanical pesticides has a significant effect on the intensity of pest attacks, the number of pest populations, and the mortality of green lice. The result of this study is that the most effective composition of botanical pesticides to reduce pest attacks on coffee plants in Dompyong village, Bendungan district, Trenggalek district is to use a composition of vegetable pesticides made from tobacco plants. For the concentration of botanical pesticides that are effective in reducing the level of damage to coffee plants caused by green lice is a concentration of 200 ml/l with an average mortality value of 20.00.